Gibbs free energy of transfer of a methylene group on {UCON + (sodium or potassium) phosphate salts} aqueous two-phase systems: Hydrophobicity effects - Silvério, Sara C. (2010)
The Gibbs free energy of transfer of a suitable hydrophobic probe can be regarded as a measure of the relative hydrophobicity of the different phases. The methylene group (CH2) can be considered hydrophobic, and thus be a suitable probe for hydrophobicity. In this work, the partition coefficients of a series of five dinitrophenylated-amino acids were experimentally determined, at 23 °C, in three different tie-lines of the biphasic systems: (UCON + K2HPO4), (UCON + potassium phosphate buffer, pH 7), (UCON + KH2PO4), (UCON + Na2HPO4), (UCON + sodium phosphate buffer, pH 7), and (UCON + NaH2PO4). The Gibbs free energy of transfer of CH2 units were calculated from the partition coefficients and used to compare the relative hydrophobicity of the equilibrium phases. The largest relative hydrophobicity was found for the ATPS formed by dihydrogen phosphate salts.